PENGELOLAAN WISATA PANTAI PANJANG DALAM PERSPEKTIF PUBLIC PRIVATE PARTNERSHIP - , Henny Aprianty; Aviko, Muksin; Evsa Wulan Suri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
he long beach tourism development program works. Based on the results of the research and discussion, it can be concluded that the collaboration between the Bengkulu Province Tourism Office and the private sector in managing Panjang Beach has provided significant economic benefits, strengthened local capacity, and encouraged innovation in responsible tourism management. This partnership prioritizes fairness, effectiveness, efficiency and sustainability, becoming a positive example of a public-private sector partnership. However, the private sector faces the challenge of complex business licensing regulations, involving various complicated requirements and procedures. The private sector invests in the construction of facilities such as hotels, restaurants, shopping centers and recreation areas, with the support of permits and regulations from the Tourism Office. Joint marketing strategy development was carried out to promote Long Beach, including social media campaigns, tourist exhibitions, and promotions through travel agents. In addition, improving facilities and services includes the provision of eight parking spots, the management of which will be determined through a technical agreement, as well as land rental contracts for traders.the long beach tourism development program works. Based on the results of the research and discussion, it can be concluded that the collaboration between the Bengkulu Province Tourism Office and the private sector in managing Panjang Beach has provided significant economic benefits, strengthened local capacity, and encouraged innovation in responsible tourism management. This partnership prioritizes fairness, effectiveness, efficiency and sustainability, becoming a positive example of a public-private sector partnership. However, the private sector faces the challenge of complex business licensing regulations, involving various complicated requirements and procedures. The private sector invests in the construction of facilities such as hotels, restaurants, shopping centers and recreation areas, with the support of permits and regulations from the Tourism Office. Joint marketing strategy development was carried out to promote Long Beach, including social media campaigns, tourist exhibitions, and promotions through travel agents. In addition, improving facilities and services includes the provision of eight parking spots, the management of which will be determined through a technical agreement, as well as land rental contracts for traders.